2016
DOI: 10.1016/j.jmii.2015.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Coexisting cytomegalovirus infection in immunocompetent patients with Clostridium difficile colitis

Abstract: Cytomegalovirus (CMV) colitis usually occurs in immunocompromised patients with human immunodeficiency virus infection, organ transplantation, and malignancy receiving chemotherapy or ulcerative colitis receiving immunosuppressive agents. However, CMV colitis is increasingly recognized in immunocompetent hosts. Notably, CMV colitis coexisting with Clostridium difficile infection (CDI) in apparently healthy individuals has been published in recent years, which could result in high morbidity and mortality. CMV c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 56 publications
0
21
0
1
Order By: Relevance
“…Conversely, our study revealed a higher rate of CMV coinfection in IBD patients with CDI and the association with poorer outcomes. A review article reported clinical scenario of coexisting cytomegalovirus infection in immunocompetent patients with CDI [ 28 ]. In cases of coexisting CMV and C. difficile colitis, ganciclovir therapy for CMV colitis in time may circumvent the unnecessary second-line therapeutic method for CDI, supposing that persistent diarrhea was not due to treatment failure for C. difficile [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, our study revealed a higher rate of CMV coinfection in IBD patients with CDI and the association with poorer outcomes. A review article reported clinical scenario of coexisting cytomegalovirus infection in immunocompetent patients with CDI [ 28 ]. In cases of coexisting CMV and C. difficile colitis, ganciclovir therapy for CMV colitis in time may circumvent the unnecessary second-line therapeutic method for CDI, supposing that persistent diarrhea was not due to treatment failure for C. difficile [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…A review article reported clinical scenario of coexisting cytomegalovirus infection in immunocompetent patients with CDI [ 28 ]. In cases of coexisting CMV and C. difficile colitis, ganciclovir therapy for CMV colitis in time may circumvent the unnecessary second-line therapeutic method for CDI, supposing that persistent diarrhea was not due to treatment failure for C. difficile [ 28 ]. In our clinical practice, coinfection is mostly seen in severe patients or those who received consequent or joined immunosuppressive medications.…”
Section: Discussionmentioning
confidence: 99%
“…Clostridium difficileassociated colitis has become a problem in the United States and was suspected despite several negative assays [23]. Negative assays do not exclude C. difficile infection, however, one should always consider other enteric infections even if pseudomembranous colitis is observed on colonoscopy [24]. Cytomegalovirus has the potential to mimic CDAC; also co-infection with multiple pathogens both in immunosuppressed and immunocompetent patients has been observed [3,25].…”
Section: Discussionmentioning
confidence: 99%
“…EBV and KSHV are associated with a range of diseases from infectious mononucleosis and lymphoma to nasopharyngeal carcinoma and Kaposi’s sarcoma. Herpesviruses such as EBV and the beta herpesvirus, cytomegalovirus (CMV), are also implicated in inflammatory bowel disease (IBD) [ 4 , 5 , 6 , 7 , 8 , 9 ]. MHV-68 infection causes a lethal sepsis in interferon gamma receptor-deficient (IFNγR −/− ) mice with large vessel vasculitis, pulmonary hemorrhage, and consolidation, while in wildtype (WT) mice MHV-68 produces a benign infection that can become latent [ 1 , 2 , 3 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gastrointestinal (GI) dilatation, also referred to as GI distension, is a clinically significant condition with diverse etiologies including IBD, Clostridium difficile colitis after antibiotic treatment, irritable bowel syndrome, diabetes, functional dyspepsia, transient constipation, parasitic infection such as giardia or nematodes, bacterial food poisoning, celiac disease, severe peptic ulcer disease, bowel obstruction, immunosuppression and, in some cases, as a complication following abdominal surgery [ 4 , 5 , 6 , 7 , 8 , 9 , 18 , 19 , 20 , 21 ]. Patients with GI dilatation experience nausea, abdominal pressure, pain, or cramping.…”
Section: Introductionmentioning
confidence: 99%